2009
DOI: 10.1002/pssr.200903225
|View full text |Cite
|
Sign up to set email alerts
|

Copper source/drain electrode contact resistance effects in amorphous indium–gallium–zinc‐oxide thin film transistors

Abstract: Since the report by Nomura et al. [1] thin film transistors (TFTs) based on amorphous oxide semiconductors (AOSs) have emerged as a promising technology, particularly for active-matrix TFT-based backplanes, due to their superior electrical performance when compared with conventional amorphous silicon and polycrystalline silicon TFTs. Among the various AOSs, amorphous indiumgallium-zinc-oxide (a-IGZO) TFTs have high field-effect mobilities exceeding that of a-Si by a factor of 10 2 , a small subthreshold swing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 6 publications
(10 reference statements)
0
25
0
Order By: Relevance
“…19) In the case of Cu, it was reported that good ohmic contact was formed between Cu and a-IGZO in the TFT annealed in ambient air. 12) However, inter-diffusion or interfacial reaction between Cu and a-IGZO during annealing may cause a change in device performance. There is a report on the contact resistance change between a metal electrode and a-IGZO, including Cu and Al in the TFT.…”
Section: Introductionmentioning
confidence: 99%
“…19) In the case of Cu, it was reported that good ohmic contact was formed between Cu and a-IGZO in the TFT annealed in ambient air. 12) However, inter-diffusion or interfacial reaction between Cu and a-IGZO during annealing may cause a change in device performance. There is a report on the contact resistance change between a metal electrode and a-IGZO, including Cu and Al in the TFT.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical property changes of the a-IGZO based TFT are closely related to the contact materials, and electrical property changes with various S/D electrode materials (Mo, Ti, Al, Au/Ti, Au-Mn, Ti/Cu, Ag, Ti/Al/Ti, Cu/Ti, Pt) have been intensively studied [9][10][11][12][13][14][15][16][17]. These results can be understood in terms of work function values, the amount of charge transfer between the electrode and the channel layer, and other factors associated with semiconductor physics [18].…”
Section: Introductionmentioning
confidence: 99%
“…The requirement of low contact resistance between electrode and semiconductor is contributed to achieve high device performance. Traditional electrode materials such as Al, Ti, ITO, Cu, and Mo have been widely used as S/D electrode . Usually, there is an interfacial reaction between oxide thin film and electrodes such as Al, Ti, and Cu, which inevitably influence device performance.…”
Section: Introductionmentioning
confidence: 99%